2011
DOI: 10.1902/jop.2010.100340
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Crestal Bone Changes Around Implants With Reduced Abutment Diameter Placed Non‐Submerged and at Subcrestal Positions: The Effect of Bone Grafting at Implant Placement

Abstract: The present study fails to demonstrate that grafting of the remaining osseous wound defect between the bone crest and the coronal aspect of the implant has a positive effect on marginal peri-implant hard-tissue changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 17 publications
4
9
0
1
Order By: Relevance
“…The very good results, histologic, clinical, and radiological, found in internal conical connection implants, when inserted in a subcrestal position, could be, in part, explained by absent or reduced presence of bacteria in the microgap of these implants 22‐28 . Several authors found no resorption of the pre‐existing crestal bone and mineralized tissues on the implant above the implant–abutment junction and overgrowing the implant shoulder 22‐28 . In the past 10 years, in our laboratory, we have extensively studied implants with a cemented implant–abutment connection.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The very good results, histologic, clinical, and radiological, found in internal conical connection implants, when inserted in a subcrestal position, could be, in part, explained by absent or reduced presence of bacteria in the microgap of these implants 22‐28 . Several authors found no resorption of the pre‐existing crestal bone and mineralized tissues on the implant above the implant–abutment junction and overgrowing the implant shoulder 22‐28 . In the past 10 years, in our laboratory, we have extensively studied implants with a cemented implant–abutment connection.…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, Dibart et al, 14 in a study using Morse cone‐connection implants, ¶¶¶¶¶ found no bacteria in the nutrient broth or in any of the implant wells and concluded that the locking taper system does not seem to allow oral bacteria to colonize the microgap (Table 2). The very good results, histologic, clinical, and radiological, found in internal conical connection implants, when inserted in a subcrestal position, could be, in part, explained by absent or reduced presence of bacteria in the microgap of these implants 22‐28 . Several authors found no resorption of the pre‐existing crestal bone and mineralized tissues on the implant above the implant–abutment junction and overgrowing the implant shoulder 22‐28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, when bone loss around the implants was evaluated, there is a controversy regarding the influence of length in these alterations, and some studies present results of larger losses in the short implants, other authors report that the length of the implant has little influence on the quantity of vertical load stress, and may have a lower effect on the distribution of stresses to bone tissue when compared to the variation in implant diameter [49,51]. In this way, Koutouzis and collaborates not found statistical difference in the values of bone resorption in larger diameter implants, comparing small diameter (3.5 mm) with larger diameter (4.5 mm) [52]. Unlike most of the cited reports, an important fact that the research revealed was the better behavior of the 3.5 mm implants when compared to the 4.0 mm diameter implants in terms of bone remodeling, that is, the smaller implants diameters showed lower bone resorption.…”
Section: Implant Dimensions (Diameter and Length)mentioning
confidence: 95%
“…The clinical significance of the present findings have not yet been evaluated. The implant system that we tested has been demonstrated both histologically and clinically minimal marginal bone loss over time, with mineralized tissue on the implant platform when the implant was placed with the IAI in subcrestal positions. Thus, the amount of endotoxin penetration from the IAI with or without placement of chlorhexidine in the internal parts of the implant might have a limited effect on marginal bone levels over time.…”
Section: Discussionmentioning
confidence: 99%